2002
DOI: 10.2136/sssaj2002.1677
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Analysis of Hog Manure and Manure‐amended Soils Using Near‐infrared Spectroscopy

Abstract: Application of hog (Sus domesticus) manure to agricultural land converts waste to fertilizer. Nevertheless, matching nutrients in highly variable manure to soil or crop needs requires analytical capability that is ideally field portable and cost‐effective. This study explored using rapid nondestructive near‐infrared spectroscopy (NIRS) to analyze nutrients in hog manure and receiving soil. Spectral data in the visible and near‐infrared (NIR) region (400–2500 nm) from manure samples were correlated with chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 10 publications
8
98
0
2
Order By: Relevance
“…However, Galassi et al (2010) did not observe a significant influence of supplementation of the diet with a mixture of 20% of wheat bran and 4% of sugar beet pulp on ammonia emissions and Triolo et al (2011) reported a high negative correlation (r=-0.952; p<0.001) between lignin content in the manure VS and its biochemical methane potential. Moreover, Bindelle et al (2009) demonstrated that the substitution of sugar beet pulp with a source of insoluble fibre, as oat hulls, decreased the synthesis of bacterial protein in the gut and the ratio faecal N:urinary N to levels similar or lower than those reached with the standard non sup- ally high which confirms the findings of other studies (Malley et al, 2002;Saeys et al, 2005;Ye et al, 2005;Sørensen et al, 2007) on the usefulness of this methodology to predict main chemical components of fresh slurry and the biochemical CH 4 potential in a range of organic substrates (Doublet et al, 2013;Triolo et al, 2014). The poor prediction for pH could be related to internal correlations to organic compounds giving no true correlations between pH and spectra absorbance peaks (Huang et al, 2007).…”
Section: Effects Of Dietary N Concentrationsupporting
confidence: 81%
See 1 more Smart Citation
“…However, Galassi et al (2010) did not observe a significant influence of supplementation of the diet with a mixture of 20% of wheat bran and 4% of sugar beet pulp on ammonia emissions and Triolo et al (2011) reported a high negative correlation (r=-0.952; p<0.001) between lignin content in the manure VS and its biochemical methane potential. Moreover, Bindelle et al (2009) demonstrated that the substitution of sugar beet pulp with a source of insoluble fibre, as oat hulls, decreased the synthesis of bacterial protein in the gut and the ratio faecal N:urinary N to levels similar or lower than those reached with the standard non sup- ally high which confirms the findings of other studies (Malley et al, 2002;Saeys et al, 2005;Ye et al, 2005;Sørensen et al, 2007) on the usefulness of this methodology to predict main chemical components of fresh slurry and the biochemical CH 4 potential in a range of organic substrates (Doublet et al, 2013;Triolo et al, 2014). The poor prediction for pH could be related to internal correlations to organic compounds giving no true correlations between pH and spectra absorbance peaks (Huang et al, 2007).…”
Section: Effects Of Dietary N Concentrationsupporting
confidence: 81%
“…Also, spectroscopic methods, as near infrared reflectance spectroscopy (NIRS) have found increasing use in the laboratory for low cost and rapid analysis, and offer a great potential for on-farm testing (Saeys et al, 2005). They have recently been applied for pig slurry analyses, and useful and accurate NIRS calibrations have been obtained for dry matter, ammonia N, total N and C (Malley et al, 2002;Saeys et al, 2005;Ye et al, 2005;Sørensen et al, 2007). Predicting methane potential emission using NIRS has also been recently a focus of interest to optimize anaerobic co-digestion processes (Doublet et al, 2013;Triolo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plot panjang gelombang dan koefisien regresi pada model DPLS dengan 7 peubah laten. (Williams dan Sobering, 1996;Malley et al, 2002;Lorenzo et al, 2009). Untuk kalibrasi model kita peroleh nilai RPD yang tinggi (RPD = 3.75).…”
Section: Hasil Dan Pembahasan Analisis Data Spektra Kopi Luwak Asli Dunclassified
“…In applications of NIR, a calibration model is a statistical correlation between the spectral data of a group of samples with the value obtained by the conventional analysis for a property (Malley et al, 2002;Brunet et al, 2007). Calibration models were generated using the modified method of least squares regression (MPLS) with the WinISI-4 software version 4.2 (Intrasoft International, LLC, 2010).…”
Section: Calibrationmentioning
confidence: 99%
“…En las aplicaciones del NIR, una calibración es un modelo de correlación estadística entre los datos espectrales de un grupo de muestras con el valor obtenido por el analisis convencional para una propiedad (Malley et al, 2002;Brunet et al, 2007). Los modelos de calibracion fueron generados utilizando el método de regresión de mínimos cuadrados modificados (MPLS) por sus siglas en inglés con el software WinISI-4 version 4.2 (Intrasoft International, LLC, 2010).…”
Section: Calibraciónunclassified